Care and education of children from zero to two years: Challenges of the work process - Valença, Sandra Mara Gonçalves; Chirelli, Mara Quaglio; da Rocha Tonhon, Silvia Franco; Pio, Danielle Abdel Massih; Cordeiro, Ana Paula [UNESP] (Ludomedia Unipessoal Lda, 2022)
The emergence of day care centers is linked to a historical context, in Brazil the new perspectives for this field of education are related to the issue of initial and continuous teacher education, in the articulation between educating and caring. Analyzing how teachers, school development assistants (ADE) and managers understand the realization of pedagogical practice and care in the education of children from zero to two years, is the focus of this investigation. Who used qualitative research, sampling and data collection in interviews and workshops with managers, teachers and school development assistants-who provide care in the municipal education units of the city surveyed. It was captured that in the process of working with the children we seek the articulation of educating and caring, the teacher plans and conducts the pedagogical process and the ADE performs care. There are divergences in the conception of caring and educating between families and school professionals; difficulties with the number of children per room, in view of meeting the needs of children; problems with infrastructure for both care and the educational process; little or no time for vocational training activities. The professionals proposed strategies to bring families closer to school and time needed for continuing education. During the investigation, it was perceived the limit of not having the view of the family, which may be the object of future research, with an expansion of the understanding of the problems and situations experienced.
Cuidado e educação de crianças de zero a dois anos: Desafios do processo de trabalho
Keywords: Child rearing; Day care center; Education; Teaching